Can an incomplete ERAS protocol reduce postoperative complications compared with conventional care in laparoscopic radical resection of colorectal cancer? A multicenter observational cohort and propensity score-matched analysis - Jian, Chenxing; Zhou, Zili; Guan, Shen; Fang, Jianying; Chen, Jinhuang; Zhao, Ning; Bao, Haijun; Li, Xianguo; Cheng, Xukai; Zhu, Wenzhong; Yang, Chunkang; Shu, Xiaogang (Frontiers in Surgery, 2022)
Background: The patients undergoing laparoscopic radical colorectomy in many Chinese hospitals do not achieve high compliance with the ERAS (enhanced recovery programs after surgery) protocol. Methods: The clinical data from 1258 patients were collected and divided into the non-ERAS and incomplete ERAS groups. Results: A total of 1169 patients were screened for inclusion. After propensity score-matched analysis (PSM), 464 pairs of well-matched patients were generated for comparative study. Incomplete ERAS reduced the incidence of postoperative complications (p=0.002), both mild (6.7% vs. 10.8%, p=0.008) and severe (3.2% vs. 6.0%, p=0.008). Statistically,incomplete ERAS reduced indirect surgical complications (27,5.8% VS59, 12.7) but not local complications (19,4.1% VS19, 4.1%).The subgroup analysis of postoperative complications revealed that all patients benefited from the incomplete ERAS protocol regardless of sex (male, p=0.037, 11.9% vs 17.9%; female, p=0.010, 5.9% vs 14.8%) or whether neoadjuvant chemotherapy was administered (neoadjuvant chemotherapy, p=0.015, 7.4% vs 24.5%; no neoadjuvant chemotherapy, p=0.018, 10.2% vs 15.8%). Younger patients (<60 y, p=0.002, 7.6% vs 17.5%) with a low BMI (<22.84, 9.4% vs 21.1%, p<0.001), smaller tumor size (<4.0 cm, 8.1% vs 18.1%, p=0.004), no fundamental diseases (8.8% vs 17.0%, p=0.007), a low ASA score (1/2, 9.7% vs 16.3%, p=0.004), proximal colon tumors (ascending/transverse colon, 12.2% vs 24.3%, p=0.027), poor (6.1% vs 23.7%, p=0.012)/moderate (10.3% vs 15.3%, p=0.034) tumor differentiation and no preoperative neoadjuvant radiotherapy (10.3% vs 16.9%, p=0.004) received more benefit from the incomplete ERAS protocol. Conclusion: The incomplete ERAS protocol decreased the incidence of postoperative complications, especially among younger patients (<60 y) with a low BMI (<22.84), smaller tumor size (<4.0 cm), no fundamental diseases, low ASA score (1/2), proximal colon tumors (ascending/transverse colon), poor/moderate differentiation and no preoperative neoadjuvant radiotherapy. ERAS should be recommended to as many patients as possible, although some will not exhibit high compliance. In the future, the core elements of ERAS need to be identified to improve the protocol.